Block k-Domination in Graphs - Suhas P. Gade; Dayanand K. Vyavahare (Utilitas Mathematica, 2025)
In this paper we introduce the concept block k-domination in graph. The block k-dominating number ????????????(G) is a minimum cardinality of k-dominating set of block graph B(G) of graph G. In this work we established upper and lower bounds on ????????????(G) in terms of elements of G and we obtain relationship between ????????????(G) and other dominating parameters of G.